Spontaneous formation of a macroscopically extended coherent state - C. Braggio; F. Chiossi; G. Carugno; A. Ortolan; G. Ruoso (Physical Review Research, 2020)
It is a straightforward result of electromagnetism that dipole oscillators radiate more strongly when they are synchronized and that if there are N dipoles, then the overall emitted intensity scales with N^{2}. In atomic physics, such an enhanced radiative property appears when coherence among two-level identical atoms is established and is well known as “superradiance.” In superfluorescence, atomic coherence develops via a self-organization process stemming from the common radiated field, starting from an incoherently prepared population inversion. In this work we establish the experimental conditions for formation of a macroscopic dipole via superfluorescence, involving the remarkable number of 4×10^{12} atoms. Self-driven atom dynamics, without the mediation of cavity QED nor quantum dots or quantum well structures, is observed in a cryogenically cooled rare-earth doped material. We present clear evidence of a decay rate that is enhanced by more than one million times compared to that of independently emitting atoms.